Secretion Management in Tracheostomized Infants using Unconventional Approaches and Outcomes: A Case Series - Shah, Hevil; Jadcherla, Sudarshan R. (American Journal of Perinatology, 2019)
Objective This study aimed to increase the understanding of secretion management in infants with tracheostomies. In this case series, we describe objective evidence for an unconventional approach in infants refractory to conventional management techniques.Study Design Case study of two NICU infants utilizing high-resolution manometry was undertaken using personalized oral stimulation protocols with fruity foods.Results Oral stimulation improved infant swallowing to clear secretions and reduce the need for suctioning.Conclusion Innovative oral stimulation protocols are needed to improve swallowing in high-risk infants.
Keywords: high-resolution manometry; dysphagia; CHARGE; aerodigestive